БІОТИЧНІ ОСОБЛИВОСТІ ЕКОСИСТЕМ СУХОГО І ГРИГОРІВСЬКОГО ЛИМАНІВ ЯК АКВАТОРІЙ МОРСЬКИХ ПОРТІВ (ПІВНІЧНО-ЗАХІДНА ЧАСТИНА ЧОРНОГО МОРЯ) - Виноградов, О.К.; Богатова, Ю.І.; Синьогуб, І.О. (Marine Ecological Journal, 2022)
Connection of the previously closed Sukhoy and Grigorievskiy limans with the sea, dredging and their transformation into the marine bays-seaports of Chernomorsk and Yuzhny led to increased biodiversity in these ecosystems. Berths disposition along the coasts and extraction of bottom sediments in ports have simplified the coastline and destroyed most of coastal biotopes and biocenoses and formathion of the ones. These ecosystems include the subsystems of pelagial, periphytal and benthal, united into a single system by the water column. «Rain» and «аnti-rain» phenomena of dead organisms bodies appeared in the pelagial because of the depth (15–22 m). Oxygen deficit, presence of hydrogen sulphide and mass mortality of bottom organisms were registered because of the great depths, the formation of a stable picnocline, the worsening of vertical water exchange and the high values of primary organic matter production under the picnocline. Representatives of brackishwater, brackish-marine and marine complexes were present in the composition of phytoand zooplankton of both limans. The belt distribution of hydrobionts was registered in the periphytal. Macrophyte algae were registered on hard substrata at preserved areas of natural shore, along with higher aquatic plants on soft sediments. Macrophytes settlements formed a coastal belt at depths up to 1.5 m. In limans, coastal shallow waters (up to 1.5 m), intermediate zones (from 2 m to 8 m) and deepwater parts of the bottom (more than 8 m) were distinguished based on the composition and biomass of macrozoobenthos. The highest biomass of macrozoobenthos was registered in shallow waters and adjacent areas of the intermediate zone. In deepwater parts of the bottom, the average biomass did not exceed 9–12 g∙m-2. The biota composition of both basins comprised 268 species of phytoplankton (similarity coefficient 31.7 %), 125 species of meso- and macrozooplankton (40 %), 80 – macrophytobenthos (78.8 %), 101 – macrozoobenthos (64.4 %) and 57 – fish (78.9 %). The biota composition of Grigorievskiy liman was richer than that of Sukhoy liman.